Uterine prolapse during pregnancy: A case report - Nóbrega, Lisieux Martins; Nóbrega, Mônica Martins; Vidal, Iaponira da Silva; Cornetta, Maria da Conceição; Gonçalves, Ana Katherine; Cobucci, Ricardo Ney (Indian Journal of Case Reports, 2018)
Pelvic organ prolapse (POP) in pregnancy is a rare condition, with potentially serious complications for both mother and fetus. The scope of complications includes urinary retention, premature delivery, fetal demise, and maternal sepsis. In this case report, we present a 35-year-old individual at 30-week gestational age with a stage 2 POP treated conservatively with bed rest in a slight Trendelenburg position, with corticosteroids and symptomatic treatment for pain relief. In this case, an innovative proposal was developed involving outpatient management with biweekly visits in prenatal care after the previously mentioned measures were carried out in 5 days that the pregnant woman was hospitalized. Conservative treatment of these patients throughout pregnancy can result in an uneventful, normal, and spontaneous delivery, as in this case where the patient evolved without complications leading to vaginal delivery occurring at 37 weeks. Early recognition of this condition is crucial and, together with proper management-related complications, such as preterm labor and trauma during delivery, can be avoided.